miR-26a-5p protects against myocardial ischemia/reperfusion injury by regulating the PTEN/PI3K/AKT signaling pathway - Xing,Xiaowei (2020)
Reperfusion strategies in acute myocardial infarction (AMI) can cause a series of additional clinical damage, defined as myocardial ischemia/reperfusion (I/R) injury, and thus there is a need for effective therapeutic methods to attenuate I/R injury. miR-26a-5p has been proven to be an essential regulator for biological processes in different cell types. Nevertheless, the role of miR-26a-5p in myocardial I/R injury has not yet been reported. We established an I/R injury model in vitro and in vivo. In vitro, we used cardiomyocytes to simulate I/R injury using hypoxia/reoxygenation (H/R) assay. In vivo, we used C57BL/6 mice to construct I/R injury model. The infarct area was examined by TTC staining. The level of miR-26a-5p and PTEN was determined by bioinformatics methods, qRT-PCR, and western blot. In addition, the viability and apoptosis of cardiomyocytes were separately detected by MTT and flow cytometry. The targeting relationship between miR-26a-5p and PTEN was analyzed by the TargetScan website and luciferase reporter assay. I/R and H/R treatment induced myocardial tissue injury and cardiomyocyte apoptosis, respectively. The results showed that miR-26a-5p was down-regulated in myocardial I/R injury. PTEN was found to be a direct target of miR-26a-5p. Furthermore, miR-26a-5p effectively improved viability and inhibited apoptosis in cardiomyocytes upon I/R injury by inhibiting PTEN expression to activate the PI3K/AKT signaling pathway. miR-26a-5p could protect cardiomyocytes against I/R injury by regulating the PTEN/PI3K/AKT pathway, which offers a potential approach for myocardial I/R injury treatment.